Designing a Competency Model for Negotiators of International Sports Contracts (Case Study: Football) - Dinarvand , Farhad; Nazari, Shahram; Norouzi Seyed Hosseini , Seyed Rasool (Journal of Foresight and Health Governance, 2026)
The purpose of this study was to design a competency model for negotiators of international football contracts. The present study was an applied developmental study conducted using a mixed-methods approach (qualitative-quantitative). The statistical population included experts, specialists, faculty members, and managers of Premier League football clubs. In the qualitative section, participants were selected using purposive and snowball sampling, and theoretical saturation was achieved with 16 participants. In the quantitative section, football-association experts, sports-law specialists, and experienced football experts familiar with sports negotiation participated. To ensure research validity, the researchers considered prolonged and continuous engagement, persistent observation, peer review, progressive subjectivity, participant involvement, and the use of multiple sources of information. Qualitative analyses were conducted through manual coding, and quantitative analyses were conducted using Expert Choice software. The results of the final coding of the interviews showed that negotiation skill, personal competency, knowledge competency, communication competency, analytical thinking and decision-making, lawfulness and legal compliance, and marketing capabilities were the main themes identified in the professional competency of international football negotiators. The prioritization of competency themes was as follows: negotiation skill, with a relative weight of 0.298, ranked first; personal competency, with a relative weight of 0.266, ranked second; and analytical thinking and decision-making, with a relative weight of 0.160, ranked third. These were followed by knowledge competency, lawfulness and legal compliance, communication competency, and marketing capabilities.